Peran kesejahteraan psikologis dan asertivitas terhadap penyesuaian perkawinan pada individu dewasa awal di Bali - Laksmi, Ni Luh Prema Shantika Putri; Wilani, Ni Made Ari (Konsorsium Psikologi Ilmiah Nusantara, 2024)
Marital adjustment is a crucial process for couples in their first five years of marriage. In Bali, the number of conflicts, domestic violence, and divorce highlight challenges in marital adjustment. This study examines the role of psychological well-being and assertiveness in marital adjustment among young adults in Bali. The sample included 94 married individuals selected through incidental sampling. This quantitative study utilized three scales: the Marital Adjustment, the Psychological Well-being, and the Assertiveness. Results from multiple linear regression analysis indicated that psychological well-being and assertiveness together accounted for 27% of the variance in marital adjustment among young adults in Bali. The findings provide insights into factors influencing marital adjustment, which may be useful for addressing marital challenges in early adulthood in Bali.